Growth-differentiation factor 15 as a predictor of mortality in patients with heart failure: a meta-analysis. Issue 2 (February 2017) - Zeng, Xiaocong; Li, Lang; Wen, Hong; Bi, Qi
Abstract : Supplemental Digital Content is available in the text Abstract : Aims: Measurement of the biomarker growth-differentiation factor 15 (GDF-15) in patients with heart failure may help in risk stratification. We assessed the relationship between GDF-15 and mortality in patients with heart failure by conducting a meta-analysis. Methods: PubMed, Embase, ISI Web of Science, SCOPUS, and Cochrane Library databases were searched for studies that reported data on the baseline GDF-15 levels and all-cause or cardiovascular mortality. Pooled hazard ratios for mortality were calculated and presented with 95% confidence intervals (CIs). Potential sources of heterogeneity were assessed by meta-regression, subgroup, and sensitivity analyses. Results: Eight studies with a total of 4126 heart failure patients were included. Pooled results showed that overexpression of GDF-15 was associated with poor survival in heart failure patients (log unit GDF-15: hazard ratio = 1.86, 95% CI = 1.37–2.52). Subgroup analyses revealed similar results. However, there was evidence of heterogeneity and publication bias. The association disappeared after correction using the trim-and-fill method (log unit GDF-15: hazard ratio 1.07, 95% CI 0.80–1.42). Conclusion: The results of this meta-analysis indicate an association of elevated GDF-15 levels with increased risk of mortality in patients with heart failure. However, the results should be interpreted with caution due to substantial heterogeneity and publication bias among the studies included in the meta-analysis.